Human Rights and Agents of Change in Iran Towards a Theory of Change (Studies in Iranian Politics,, 2018)
This volume extends debates on the interaction between universal human rights and the political experiences of Iranians, through a conceptual analysis of 'theories of change'. It assesses the practical processes by which individuals, organizations and movements can reform or impact the structural, theological, and political challenges faced in the Iranian context. Contributors to this volume investigate how structures, institutions, and agents in Iran maneuver for influence and power at the state level, through the law, in international corridors, at the grassroots, and by implementing multiple and complex methods. The chapters provide distinct but interrelated analysis of key drivers of change in Iran. A number of those operate primarily through top-down approaches, such as the political reform movement, lawyers pursuing legislative change, and international human rights monitoring bodies. Others take a bottom-up approach, including local movements and campaigns such as the women's movement, the student movement, and ethnic minority groups. Rebecca Barlow is a Senior Research Fellow at the Alfred Deakin Institute for Citizenship and Globalisation, Deakin University, Australia. Her research focuses on the Iranian women's movement and the politics of human rights in the Islamic Republic of Iran. Dr. Barlow is the author of Universal Women's Human Rights and the Muslim Question: Iran's One Million Signatures Campaign (2012). She has worked for the Victorian Local Governance Association to produce a toolkit to implement the 'Victorian Charter of Human Rights and Responsibilities'. She has also interned and acted as Consultant for the United Nations Population Fund (UNFPA) Gender, Human Rights and Culture Branch, working on the United Nations Global Forum of Faith-based Organisations in Population and Development (2008). Shahram Akbarzadeh is Professor of Middle East & Central Asian Politics at the Alfred Deakin Institute for Citizenship and Globalisation, Deakin University, Australia. Prof. Akbarzadeh is author of Uzbekistan and the United States (2005), US Foreign Policy in the Middle East (2008 with Kylie Baxter) and Muslim Active Citizenship in the West (2014 with Mario Peucker). He is the founding Editor of the Islamic Studies Series and a regular public commentator.